Pedicled adipofascial infraclavicular flap: Elevation technique and its use for maintaining neck contour and vessel coverage after radical and modified radical neck dissection. Issue 10 (29th April 2016) - Yoo, John; Low, Tsu‐Hui (Hubert); Tam, Samantha; Partridge, Allison; MacNeil, S. Danielle; Nichols, Anthony C.; Fung, Kevin
ABSTRACT: Background: The pedicled adipofascial infraclavicular flap (ICF) is based on the anterior perforator of the supraclavicular artery and supplies the fasciocutaneous tissue of the upper chest. This flap may be used to address neck contour defects and vessel coverage after radical and modified radical neck dissections (MRNDs). Methods: We described the pedicled adipofascial ICF elevation technique and its use immediately after neck dissections in order to maintain soft tissue volume and vessel coverage. A video of the operation is provided. Results: Our results demonstrated satisfactory neck contours with adequate volume replacement, great vessel coverage, and little donor‐site morbidity. Conclusion: The pedicled adipofascial ICF is a technically straightforward operation with broad possible applications in head and neck surgery. It may be useful to provide vascularized soft‐tissue coverage and maintain neck contour after neck dissections. © 2016 Wiley Periodicals, Inc. Head Neck 38: First–1582, 2016